Anti-human CD63 monoclonal antibody COS3A upregulates monocyte-induced IL-10 excretion leading to diminution of CD3-mediated T cell response. (October 2019) - Wansook, Siriwan; Mahasongkram, Kodchakorn; Chruekamlow, Nuttaphol; Pata, Supansa; Kasinrerk, Watchara; Khunkaewla, Panida
Highlights: Anti-CD63 mAb COS3A inhibits CD3-mediated T-cell activation in a requirement of APCs. Soluble anti-CD63 mAb reduces IL-2, INF-γ secretion and surface CD25 on T-cells during T cell activation. Anti-CD63 mAb COS3A induced increased production of IL-10, resulting in suppression of T-cell activation. Abstract: Human CD63 has been reported to play a role either as an inhibitor or as a co-stimulator of T- cell responses, although the mechanism of this is unclear. In this study, an anti-human CD63 monoclonal antibody (mAb) COS3A was used to monitor the role of CD63 in T-cell activation. MAb COS3A could inhibit CD3-mediated T-cell proliferation and CD25 expression in peripheral blood mononuclear cells (PBMCs), used as a study model, but the suppressive effect was not observed when purified T-cells were used instead of PBMCs. The inhibitory phenomenon was associated with downregulation of IL-2 and IFN-γ by T-cells, but upregulation of IL-10 by monocytes. Neutralizing IL-10 with anti-IL-10 mAb improved the T-cell response, indicating the role of IL-10 in T-cell suppression. In this study, monocytes were demonstrated to play a role in impeding T-cell activation by the anti-CD63 mAb COS3A. This is the first evidence that anti-CD63 mAb induces IL-10 secretion by monocytes, which later play a role in T-cell hypo-responsiveness.